Processing and characterization of organic PU foam reinforced with nano particles. (2021) - Vinoth Kumar, S.; Subramanian, Jeyanthi; Giridharan, A.; Gupta, Manshu; Adhikari, Aparna; Gayen, Mishelle
Abstract: A flexible nano composite was synthesized using a mechanical agitator mixing process and reinforced with different wt.% of multi-walled carbon nano tubes, bamboo charcoal, and cupric oxide by absorption and hydrothermal reduction process. These foams have been studied and analyzed based on their physical behavioural property. The studies reveal that the nano fillers have brought exemplary advancements in the field of material science and application. Through the dielectric test, the determination of the electrical conductivity of the nano composite is done. Field Emission Scanning Electron Microscope (FESEM) has been used for observing the morphology, and images show homogeneity due to hydrothermal reduction process. The thermal stability of the nano composite foam was observed through Thermogravimetric Analysis (TGA). A drastic improvement can be seen in the thermal stability and electrical conductivity by adding small amount of nano particle reinforcement in the organic PU foam.